Development of an Objective Model to Define Near-Term Risk of Ileocecal Resection in Patients with Terminal Ileal Crohn Disease. Issue 11 (3rd May 2019) - Grass, Fabian; Fletcher, Joel G; Alsughayer, Ahmad; Petersen, Molly; Bruining, David H; Bartlett, David J; Mathis, Kellie L; Lightner, Amy L
Abstract: Background: The decision to either escalate medical therapy or proceed to ileocecal resection (ICR) in patients with terminal ileal Crohn disease (CD) remains largely subjective. We sought to develop a risk score for predicting ICR at 1 year from computed tomography or magnetic resonance enterography (CTE/MRE). Methods: We conducted a retrospective cohort study including all consecutive adult (> 18 years) patients with imaging findings of terminal ileal CD (Montreal classification: B1, inflammatory predominant; B2, stricturing; or B3, penetrating) on CTE/MRE between January 1, 2016, and December 31, 2016. The risk for ICR at 6 months and at 1 year of CTE/MRE and risk factors associated with ICR, including demographics, CD-specific immunosuppressive therapeutics, and disease presentation at the time of imaging, were determined. Results: Of 559 patients, 121 (21.6%) underwent ICR during follow-up (1.4 years [IQR 0.21–1.64 years]); the risk for ICR at 6 months and at 1 year was 18.2% (95% CI 14.7%–21.6%) and 20.5% (95% CI 16.8%–24.1%), respectively. Multivariable analysis revealed Montreal classification (B2, hazard ratio [HR] 2.73, and B3, HR 6.80, both P < 0.0001), upstream bowel dilation (HR 3.06, P < 0.0001), and younger age (19–29 years reference, 30–44 years, HR 0.83 [ P = 0.40]; 45–59 years, HR 0.58 [ P = 0.04], and 60+ years, HR 0.45 [ P = 0.01]) to significantly increase the likelihood of ICR. A predictive nomogram for interval ICR was developed based on these significant variables. Conclusions: The presence of CD strictures, penetrating complications, and upstream bowel dilation on CTE/MRE, combined with young age, significantly predict ICR. The suggested risk model may facilitate objective therapeutic decision-making. Abstract : Our findings indicate that for patients with terminal ileal Crohn's disease, the presence of terminal ileal stricture or terminal ileal penetrating findings, upstream bowel dilation and young age are associated with significant surgical risk within the next year.